Phylogenomic analyses in the complex Neotropical subfamily Corydoradinae (Siluriformes: Callichthyidae) with a new classification based on morphological and molecular data - Dias, Angelica C. [UNESP]; Tencatt, Luiz F.C.; Roxo, Fabio F.; da Costa Silva, Gabriel de Souza [UNESP]; Santos, Sérgio A.; Britto, Marcelo R.; Taylor, Martin I.; Oliveira, Claudio [UNESP] (Oxford University Press (OUP), 2025)
The family Callichthyidae, which comprises the subfamilies Corydoradinae and Callichthyinae, represents one of the largest families within the Siluriformes. Corydoradinae, the largest subfamily of Callichthyidae, alone accounts for >200 valid species, with new species being described frequently. This subfamily holds significant popularity among catfish enthusiasts worldwide, mainly because Corydoras are small, peaceful, and colourful fishes. Recognizing the existence of polyphyletic groups within Corydoradinae, the aim of this study was to construct a new phylogenetic hypothesis using genomic data (ultraconserved elements) and to re-evaluate the synonymized genera using the most recent morphological data. Our results supported the monophyly of Corydoradinae and identified seven distinct groups of species, each one with an associated preavailable generic name. These genera, namely Corydoras, Aspidoras, Scleromystax, Gastrodermus (resurrected), Osteogaster (resurrected), Brochis (resurrected), and Hoplisoma (resurrected), were all validated based on evidence derived from molecular and morphological analyses. A taxonomic key for the Corydoradinae genera is provided.
Keywords: biodiversity; catfish; Corydoras; phylogenomics; phylogeny; systematics; taxonomy; ultraconserved element